¿Cómo es el sujeto? Crítica y clínica en los poemas de Oliverio Girondo - Vich, Víctor (Pontificia Universidad Católica del Perú, 2022)
This essay studies the representation of subjectivity in Oliverio Girondo’s poetry based on three types of figurations: the decentering of identity, the crisis of the will and the death drive. The analysis attempts to show, on the one hand, the importance that these representations had in a context that demanded unitary, coherent and productive subjects and, on the other hand, to locate the critique that this poetry addresses to modern reason. The essay lists the strategies elucidated to reconfigure subjectivity before the world, before language and before itself.

Este ensayo estudia la representación de la subjetividad en la poesía de Oliverio Girondo a partir de tres tipos de figuraciones: el descentramiento de la identidad, la crisis de la voluntad y la pulsión de muerte. En el análisis se intenta mostrar, por un lado, la importancia que estas representaciones tuvieron en un contexto que exigía sujetos unitarios, coherentes y productivos, y, por otro, localizar la crítica que esta poesía le dirige a la razón moderna. El ensayo enumera las estrategias que se elucidan para reconfigurar la subjetividad ante el mundo, ante el lenguaje y ante sí misma.
What Is the Subject Like? Critical and Clinical in the Poems of Oliverio Girondo
Keywords: Girondo; Modernity; Subject; Decentering; Death drive; Girondo; Modernidad; Sujeto; Descentramiento; Pulsión de muerte; https://purl.org/pe-repo/ocde/ford#6.02.06